Multi-level lot sizing: A literature survey - Alf Kimms; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1996)
Lot sizing certainly belongs to the most established production planning problems. First scientific reports of this subject date from the beginning of the 20th century and at least one chapter about lot sizing can be found in almost every good textbook about production research issues. But, as we will show, some topics of practical importance such as multi-level lot sizing where capacity is scarce and demand is time variant have first been successfully attacked in the recent past. Furthermore, lot size and sequence decisions are usually not integrated as it ought to be for the short-term planning. This paper reviews the history of multi-level lot sizing from the very early work to the state-of-the-art.
Keywords: 650